Reducing sugar-fatty amine adhesive and application thereof

The adhesive is prepared in one step by reducing sugar and Maillard reaction of specific structural fatty amines, which solves the environmental and health hazards of formaldehyde resins, and realizes the production of low-cost, low-heat pressure adhesives, and has excellent bonding It has water resistance and is suitable for industrial production of wood and bamboo, promoting the sustainable development of the artificial board industry.

CN119264846APending Publication Date: 2025-01-07SOUTHWEST FORESTRY UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411615146.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The presence of formaldehyde resins in existing wood and bamboo adhesives leads to environmental and health hazards. The high heat pressing temperature is not suitable for industrial production. The traditional methods are complex and costly, and they fail to effectively utilize the potential of reducing sugar.

Method used

The adhesive is prepared by reacting reducing sugar with a fatty amine with a specific structure through Maillard in one step, avoiding high temperature and long-term polymerization, low curing temperature, and not changing the structure of the reducing sugar. Water is used as a solvent, which is suitable for large-scale production.

Benefits of technology

It has achieved formaldehyde-free, low-cost and stable adhesive, excellent adhesive properties and water resistance, and is suitable for industrial production of wood and bamboo, promoting the green and sustainable development of the artificial board industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264846A_ABST
    Figure CN119264846A_ABST
Patent Text Reader

Abstract

The invention discloses a reducing sugar-fatty amine adhesive which is prepared by the following steps: adding fatty amine into a reducing sugar aqueous solution with the mass concentration of 20-60%, uniformly mixing, and reacting in a water bath at 40-60 DEG C for 10-60 minutes or stirring at room temperature for 24-48 hours, the curing temperature of the adhesive is 100-140 DEG C. The adhesive disclosed by the invention has the advantages of simplicity in preparation, low price, easily available raw materials, no formaldehyde release, excellent performance, low curing temperature and the like, and when the reducing sugar-aliphatic amine adhesive is applied to wood and bamboo bonding, excellent bonding strength and water resistance are shown; the adhesive is suitable for industrial popularization and application in the production field of plywood and shaving boards.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wood and bamboo material processing and production, and specifically relates to a reducing sugar-fatty amine adhesive and application thereof. Background Art

[0002] At present, among the adhesives used in the artificial board industry, traditional formaldehyde resins such as urea-formaldehyde resin adhesives (UF), melamine-formaldehyde resin adhesives (MF) and phenolic resin adhesives (PF) are the main ones. However, since the addition and polycondensation reactions of the resins are reversible reactions, the resins will continue to depolymerize and release formaldehyde during use; at the same time, the use of formaldehyde as a synthetic raw material directly leads to the presence of unreacted formaldehyde in the synthesized resin. Therefore, since formaldehyde was defined as a Class I carcinogen, scholars and industries around the world have begun to look for formaldehyde-free adhesives in order to eventually replace formaldehyde-based resins, thereby reducing harm to the environment and human health.

[0003] The Maillard reaction originally refers to the reaction between reducing sugars and amino compounds (proteins and amino acids). This reaction was first reported by French chemist Louis-Camille Maillard in 1912. The Maillard reaction is widely used in the food field. A series of products are formed through the complex reaction of reducing sugars with proteins or amino acids, thereby improving the appearance and taste of food. However, in the field of wood and bamboo adhesives, although sugar compounds are one of the most abundant natural products on the earth and have significant industrial application potential, the application research of sugar-based adhesives based on the Maillard reaction is still relatively limited. Although many amino compounds can undergo the Maillard reaction with reducing sugars, due to the differences in the structure of amino compounds, the performance of the final adhesive will also be significantly different. What kind of structure can produce excellent bonding performance is still unclear, so there is a lack of clear guidance for the selection of raw materials. This is also the main reason why the potential of reducing sugar as a raw material for adhesive preparation has not been fully explored.

[0004] In the prior art, CN114958286A discloses a sucrose-based wood adhesive based on the Maillard reaction and a preparation method thereof. However, since sucrose itself is not a reducing sugar, the invention relies on the preliminary oxidation treatment of sucrose to obtain a hydroformylation syrup to achieve further polymerization with a branched polyamine. At the same time, the synthesis process of the branched polyamine disclosed in the application is relatively complicated, involving multi-step polymerization reactions, which is not conducive to actual production applications. CN115785899A and CN117757417A disclose a maltose-based and a lactose-based hyperbranched boiling water-resistant adhesive and a preparation method thereof, respectively. A boiling water-resistant wood adhesive is prepared by reacting two reducing sugars with tri(2-aminoethyl)amine and polyethyleneimine, respectively. At the same time, the patent applicants also reported in "Preparation a novel high performance glucose-based wood adhesive with hyperbranched cross-linked network by air oxidation." Polymer Testing 126(2023):108157." and "Novel hyperbranched resin for wood adhesive: Based on airoxidation and crosslinking copolymerization strategy." Polymer Testing 126(2023):108154." that boiling water-resistant wood adhesives are prepared by reacting tri(2-aminoethyl)amine and polyethyleneimine with glucose, respectively. The water resistance of these adhesives depends on the cross-linking and curing of aldehyde compounds generated by oxidation of sugar compounds by oxygen in the air during preparation and hot pressing with polyamino compounds. However, after oxidation, the structure of reducing sugars is destroyed and loses its reducing property. Therefore, these adhesives are not essentially prepared through the Maillard reaction. Prolonging the reaction time and increasing the hot pressing temperature can help generate more aldehyde compounds, thereby increasing the cross-linking density of the cured network. Therefore, these adhesives can only show good water resistance through long-term polymerization at high temperature (80°C, 1-5h) and at high hot pressing temperatures (180-220°C). However, in the industrial production of artificial boards, high hot pressing temperatures are demanding on equipment and consume a lot of energy. In particular, the use of hot pressing temperatures above 130°C in plywood production will lead to a significant increase in the rate of board explosion. Therefore, high hot pressing temperatures (180-220°C) are not suitable for industrial production. In addition, the above-mentioned adhesives do not involve their performance in bamboo gluing.At present, bamboo-based composite materials still rely on PF, isocyanate and other resins as the main adhesives to solve the shortcomings of bamboo such as low porosity, poor permeability and poor surface wettability, but the cost of adhesives and safety of use still exist. Therefore, it is urgent to develop an adhesive system with easy-to-obtain raw materials, simple and green preparation, low cost and suitable for large-scale production, so as to achieve the technical upgrade of wood-bamboo gluing products and promote the sustainable development of the wood-based panel industry. Summary of the invention

[0005] In order to solve the problems of the prior art, the present invention provides a reducing sugar-fatty amine adhesive, which selects safe and non-toxic reducing sugar compounds as raw materials, and reacts with fatty amines through the Maillard reaction to obtain an adhesive with excellent bonding performance in one step. The reducing sugar is a renewable biomass raw material with a wide source and low price. It is proposed that the selection of aliphatic linear diamines or branched polyamines must meet the corresponding structural requirements to ensure the performance of the adhesive. Water is used as a solvent for the reaction, and no organic solvent is required, which is green and environmentally friendly. In the application of wood and bamboo bonding, the adhesive has the characteristics of no formaldehyde release, good storage stability, low curing temperature, low cost and excellent bonding performance.

[0006] Different from the reported technologies, the method of the present invention directly causes Maillard reaction between reducing sugar and fatty amine without changing the structure of reducing sugar itself, and the reaction can be carried out at room temperature or 40-60°C, without the need for long-term high-temperature polymerization. Based on the selection of fatty amines with specific structures, the prepared adhesive can be quickly cured at 100-140°C, or gradually cured at room temperature, and the cured product has excellent water resistance, so high-temperature hot pressing can be avoided in the production of artificial boards.

[0007] The preparation of the reducing sugar-fatty amine wood and bamboo adhesive of the present invention is as follows:

[0008] (1) accurately weighing reducing sugar, mixing the reducing sugar with a solvent in a certain proportion to prepare a uniform reducing sugar solution with a mass concentration of 20-60%;

[0009] The reducing sugar is one of glucose, maltose, galactose, fructose, mannose, hydrolyzed starch, hydrolyzed cellulose, hydrolyzed sucrose, hydrolyzed peach gum, and hydrolyzed sugarcane molasses; the solvent is deionized water or tap water;

[0010] (2) adding a fatty amine to the reducing sugar solution of step (1), and placing the mixture in a water bath at 40-60° C. for reaction for 10-60 min or stirring at room temperature for 24-48 h to obtain a wood and bamboo adhesive;

[0011] The fatty amine is a linear diamine or polyamine, including 1,6-hexanediamine, tris(2-aminoethyl)amine, and melamine-1,6-hexanediamine polymer; the mass ratio of the fatty amine to the reducing sugar is 1:0.5-5.0;

[0012] Linear diamines: And there are no adjacent amino groups in the carbon chain; for example:

[0013]

[0014] Branched polyamine: There are no adjacent active hydrogen-containing amino groups in the carbon chain, for example:

[0015] Tris(2-aminoethyl)amine: Melamine-1,6-hexanediamine polymer (n≥90):

[0016]

[0017] The melamine-1,6-hexanediamine polymer is prepared by reacting melamine and 1,6-hexanediamine under the action of an acidic catalyst at 180-220° C., and the molar ratio of melamine to 1,6-hexanediamine is 1.0:2.0-4.0.

[0018] The theoretical solid content of the adhesive prepared by the invention is maintained at 40%-70%, and the curing temperature range is 100-140°C.

[0019] Another object of the present invention is to apply the reducing sugar-fatty amine adhesive to the bonding of wood and bamboo materials.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] (1) The present invention avoids the technical barriers and cost increase caused by reducing sugar modification in the traditional method, and proposes to select aliphatic diamines or branched polyamines with specific structures and reducing sugars to prepare a high-performance wood and bamboo adhesive in one step, which has the advantages of low technical difficulty and easy promotion;

[0022] (2) The reducing sugars involved in the present invention are widely available and inexpensive, thus meeting the requirements of large-scale production;

[0023] (3) The adhesive of the present invention does not require any modification treatment, has a simple preparation process, and is low in cost; the curing temperature is low (100-140° C.), which can avoid the problem of increased board bursting rate caused by high hot pressing temperature in industrial production. The adhesive of the present invention is more suitable for industrial production and promotion;

[0024] (4) The adhesive of the present invention does not release formaldehyde, has excellent water resistance, can be used for bonding wood and bamboo, can achieve high-value utilization of biomass resources, and has significant potential in promoting the green and sustainable development of the wood-based panel industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a physical schematic diagram of the adhesive in Examples 1-3;

[0026] Figure 2 The NMR of the melamine-1,6-hexanediamine polymer-glucose adhesive in Example 1 is 13 C spectrum;

[0027] Figure 3 The solid state NMR of the melamine-1,6-hexanediamine polymer-glucose adhesive in Example 1 is 13 C spectrum;

[0028] Figure 4 is the gel permeation chromatogram of the melamine-1,6-hexanediamine polymer-glucose adhesive in Example 1;

[0029] Figure 5 is the thermogravimetric analysis curve of the melamine-1,6-hexanediamine polymer-glucose adhesive in Example 1;

[0030] Figure 6 A photo of bamboo cracks bonded to bamboo material in Example 1;

[0031] Figure 7 is a physical picture of the adhesive in Examples 6-8;

[0032] Figure 8 is the nuclear magnetic resonance of 1,6-hexanediamine-glucose adhesive (mass ratio is 2.0) in Example 6 13 C spectrum;

[0033] Fig. 9 The solid state nuclear magnetic resonance of 1,6-hexanediamine-glucose adhesive (mass ratio is 2.0) in Example 6 13 C spectrum;

[0034] Fig.10 is the mass spectrum of 1,6-hexanediamine-glucose adhesive (mass ratio is 2.0) in Example 6;

[0035] Fig.11 is the gel permeation chromatogram of 1,6-hexanediamine-glucose adhesive (mass ratio is 2.0) in Example 6;

[0036] Fig.12 This is a photo of the finished product of multi-layer plywood;

[0037] Fig.13 This is a photo of the curing of ethylenediamine-glucose adhesive. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below by way of examples, but the protection scope of the present invention is not limited to the contents described above. The methods in the examples are conventional methods unless otherwise specified, and the reagents used are conventional commercially available reagents or reagents prepared according to conventional methods unless otherwise specified;

[0039] In the following examples, the melamine-1,6-hexanediamine polymer is prepared by reacting melamine and 1,6-hexanediamine at 200° C. in the presence of an acidic catalyst (NH 4 Cl, added in an amount of 6% of the mass of melamine), wherein the molar ratio of melamine to 1,6-hexanediamine is 1:3;

[0040] Example 1: Preparation of adhesive using melamine-1,6-hexanediamine polymer and glucose as raw materials

[0041] (1) At room temperature, accurately weigh 6 g of glucose, mix and dissolve the glucose with deionized water to prepare a uniform aqueous solution with a mass concentration of 42.9%;

[0042] (2) Add 6 g of melamine-1,6-hexanediamine polymer (MH-3.0) to the glucose solution in step (1), mix well and place in a 60° C. water bath for 10 min to obtain a reducing sugar-fatty amine adhesive (MHG-1.0) ( Figure 1 ), Liquid NMR of Adhesives 13 C spectrum Figure 2 , where the NMR signal corresponding to C1 in glucose almost completely disappears. At the same time, when the adhesive is completely cured, its solid NMR 13 C spectrum ( Figure 3 ) also almost completely disappeared at 60-100 ppm corresponding to the carbon atoms on glucose, indicating that the melamine-1,6-hexanediamine polymer and glucose were polymerized; gel permeation chromatogram ( Figure 4 The significantly increased molecular weight of the adhesive MHG-1.0 in ) further confirmed that the two had polymerized. Thermogravimetric analysis curve ( Figure 5 ) shows that the thermal decomposition temperature of more than 450 °C indicates that the adhesive has a highly cross-linked cured network after curing.

[0043] (3) The adhesive of this embodiment was used to bond bamboo sheets with a thickness of 2 mm, and the performance test of the overlap of two layers of bamboo sheets was carried out. When the hot pressing temperature was 140°C, the hot pressing time was 6 minutes, and the hot pressing pressure was 1.0 MPa, the results were as follows: Figure 6 It can be seen from the figure that 100% of the bamboo in the dry bamboo bonding specimen has been broken, indicating that the adhesive of this embodiment has excellent bamboo bonding performance.

[0044] Example 2: Preparation of adhesive using melamine-1,6-hexanediamine polymer and maltose as raw materials

[0045] (1) At room temperature, accurately weigh 6 g of maltose, mix and dissolve the maltose with deionized water to prepare a uniform aqueous solution with a mass concentration of 42.9%;

[0046] (2) Add 6 g of melamine-1,6-hexanediamine polymer (same as in Example 1) to the maltose solution in step (1), mix well and place in a 60° C. water bath for 10 min to obtain a reducing sugar-fatty amine adhesive ( Figure 1 ).

[0047] Example 3: Preparation of adhesive using melamine-1,6-hexanediamine polymer and hydrolyzed starch as raw materials

[0048] (1) At room temperature, 6 g of cassava starch was accurately weighed into a single-necked flask, 8 g of deionized water was added to prepare a solution with a mass concentration of 42.9%, and then 0.42 g of hydrochloric acid was added. The mixture was reacted in a water bath at 90° C. under mechanical stirring for 3 h to obtain a hydrolyzed starch solution;

[0049] (2) Add 6 g of melamine-1,6-hexanediamine polymer to the hydrolyzed starch solution of step (1), mix well and place in a 60° C. water bath for 10 min to obtain a reducing sugar-fatty amine adhesive ( Figure 1 ).

[0050] Example 4: Preparation of adhesive using melamine-1,6-hexanediamine polymer and galactose as raw materials

[0051] (1) At room temperature, accurately weigh 6 g of galactose, mix and dissolve the galactose with deionized water to prepare a uniform aqueous solution with a mass concentration of 42.9%;

[0052] (2) Add 6 g of melamine-1,6-hexanediamine polymer to the galactose solution of step (1), mix well and place in a 60° C. water bath to react for 10 min to obtain a reducing sugar-fatty amine adhesive.

[0053] Example 5: Preparation of adhesive using melamine-1,6-hexanediamine polymer and mannose as raw materials

[0054] (1) At room temperature, accurately weigh 6 g of mannose, mix and dissolve the mannose with deionized water to prepare a uniform aqueous solution with a mass concentration of 42.9%;

[0055] (2) Add 6 g of melamine-1,6-hexanediamine polymer to the mannose solution in step (1), mix well, and place in a 60° C. water bath to react for 10 min to obtain a reducing sugar-fatty amine adhesive.

[0056] Performance test experiment of the adhesives prepared in the above examples 1-5:

[0057] A. Take the adhesives prepared in Examples 1-3 respectively, and use birch veneer with a thickness of 2 mm to press three-layer plywood (the amount of glue applied is 250 g / m 2 , the hot pressing time is 6 minutes, the hot pressing temperatures are 120°C and 140°C respectively, and the hot pressing pressure is 1.0MPa), and the water resistance of the board is tested according to the national standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels". The results are shown in Table 1. It can be seen from the table that when the hot pressing temperature is 120°C, the adhesives prepared in Examples 1-3 have reached the requirements for water resistance of Class III plywood in the national standard. When the hot pressing temperature is raised to 140°C, the water resistance of the adhesives prepared in Examples 1-3 is further improved, far exceeding the requirements for water resistance of Class II plywood in the national standard (>0.7MPa);

[0058] Table 1 Test results of water resistance of three-layer plywood

[0059]

[0060] B. Take the adhesives prepared in Examples 1-3 respectively, and use a bamboo with a thickness of 2 mm to perform a performance test on the overlap of two layers of bamboo pieces (the hot pressing time is 6 minutes, the hot pressing temperature is 120°C and 140°C, and the hot pressing pressure is 1.0 MPa), and perform a water resistance test on them. The results are shown in Table 2. It can be seen from the table that the adhesives prepared in Examples 1-3 have excellent bonding properties and water resistance for bamboo. Under the hot pressing condition of 120°C, Example 1 has boiling water resistance. As the hot pressing temperature is increased to 140°C, the adhesives prepared in Examples 1-3 all show excellent boiling water resistance for bamboo;

[0061] Table 2 Test results of two-layer bamboo overlap performance

[0063]

[0064] C. Take the adhesives prepared in Examples 4-5 respectively, and use poplar veneer with a thickness of 2 mm to press three-layer plywood (the amount of glue applied is 250 g / m 2 , the hot pressing time is 6 minutes, the hot pressing temperature is 120℃ and 140℃, and the hot pressing pressure is 1.0MPa). According to the national standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", the water resistance of the board is tested. The results are shown in Table 3. It can be seen from the table that adhesives with similar bonding properties can be prepared by reacting the same fatty amine with different reducing sugars; the adhesives prepared in Examples 4-5 meet the national standard requirements for water resistance of II plywood at 120 and 140℃ (>0.7MPa);

[0065] Table 3 Water resistance test results of three-layer plywood

[0066]

[0067] Example 6: Preparation of adhesive using 1,6-hexanediamine and glucose as raw materials

[0068] (1) At room temperature, accurately weigh 8 g of glucose, mix and dissolve the glucose with deionized water to prepare a uniform aqueous solution with a mass concentration of 50%;

[0069] (2) Add 4 g of 1,6-hexanediamine to the glucose solution in step (1), and place in a 60° C. water bath for reaction for 10 min and 30 min to obtain reducing sugar-fatty amine adhesives (HG-2.0-10, HG-2.0-30) ( Figure 7 ), Liquid NMR of Adhesives 13 C spectrum ( Figure 8 ) completely disappears, and when the adhesive is completely cured, its solid-state NMR 13 C spectrum ( Fig. 9 ) The signal corresponding to the carbon atom on glucose at 60-100 ppm also almost completely disappeared, indicating that 1,6-hexanediamine and glucose were polymerized. Fig.10 ) and the molecular ion peaks at 261 and 279 Da in gel permeation chromatography ( Fig.11 This is further confirmed by the significantly increased molecular weight of adhesives (HG-2.0-10 and HG-2.0-30) corresponding to different reaction times in the experiment.

[0070] Example 7: Preparation of adhesive using 1,6-hexanediamine and maltose as raw materials

[0071] (1) At room temperature, accurately weigh 8 g of maltose, mix and dissolve the maltose with deionized water to prepare a uniform aqueous solution with a mass concentration of 50%;

[0072] (2) Add 4 g of 1,6-hexanediamine to the maltose solution in step (1), and place in a 60° C. water bath for reaction for 10 min to obtain a reducing sugar-fatty amine adhesive ( Figure 7 ).

[0073] Example 8: Preparation of adhesive using 1,6-hexanediamine polymer and hydrolyzed starch as raw materials

[0074] (1) At room temperature, accurately weigh 8 g of cassava starch into a single-necked flask, add 8 g of deionized water to prepare a solution with a mass concentration of 50%, then add 0.42 g of hydrochloric acid, place in a 90° C. water bath, and react for 3 h under mechanical stirring to obtain a hydrolyzed starch solution;

[0075] (2) Add 4 g of 1,6-hexanediamine to the hydrolyzed starch solution of step (1), place in a 60° C. water bath and react for 10 min to obtain a reducing sugar-fatty amine adhesive ( Figure 7 ).

[0076] Performance test experiment of the adhesives prepared in the above Examples 6-8:

[0077] The adhesives prepared in Examples 6-8 were respectively taken, and the overlapping performance of two layers of bamboo pieces with a thickness of 2 mm was tested (the hot pressing time was 6 minutes, and the hot pressing temperature was 120°C and 140°C), and the water resistance was tested. The results are shown in Table 4. It can be seen from the table that the diamine without adjacent amino groups in the carbon chain can also be used to prepare high-performance adhesives with reducing sugars. When the hot pressing temperature is 140°C, the boiling water resistant bonding strength of the adhesives prepared in Examples 6-8 has reached more than 3.0 MPa;

[0078] Table 4 Test results of two-layer bamboo overlap performance

[0079]

[0080] Example 9: Preparation of adhesive using 1,6-hexanediamine or melamine-1,6-hexanediamine polymer and glucose as raw materials

[0081] (1) At room temperature, accurately weigh two portions of glucose, each weighing 8 g, and mix and dissolve the glucose in deionized water to prepare uniform aqueous solutions with mass concentrations of 50% and 42.9%, respectively;

[0082] (2) adding 4 g of 1,6-hexanediamine to the 50% glucose solution in step (1), and mechanically stirring at room temperature for 48 h, or adding 8 g of melamine-1,6-hexanediamine polymer to the 42.9% glucose solution in step (1), and mechanically stirring at room temperature for 24 h, to obtain a reducing sugar-fatty amine adhesive;

[0083] Take the above adhesive and press three layers of plywood with 2mm thick birch veneer (the glue amount is 250g / m 2 , hot pressing time is 6 minutes, hot pressing temperature is 120℃ and 140℃ respectively, hot pressing pressure is 1.0MPa), according to the national standard GB / T17657-2022 "Test method for physical and chemical properties of artificial board and veneer artificial board", the water resistance of the board is tested, and the results are shown in Table 5. It can be seen from the table that the adhesive prepared at room temperature still shows excellent water resistance, and its water resistance is equivalent to that of the adhesive prepared by heating in Example 1, which further confirms that the adhesive of the present invention can be prepared at room temperature. When the hot pressing temperature is only 120℃, the water resistance of the adhesive has met the national standard requirements for the water resistance of Class II plywood (>0.7MPa);

[0084] Table 5 Water resistance test results of three-layer plywood

[0085]

[0086] Example 10: The preparation method of this example is the same as that of Example 1, except that a 30 kg reactor is used to prepare melamine-1,6-hexanediamine polymer, and 500 kg reducing sugar-fatty amine adhesive is prepared with glucose. The adhesive is tested on a plywood production line in a plywood enterprise to press multi-layer plywood;

[0087] Take the adhesive prepared in this example and use 1.8 mm thick eucalyptus veneer to prepare seven-layer plywood ( Fig.12 )(Hot pressing time is 30min, hot pressing temperature is 105℃ and 110℃ respectively), according to national standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels" and GB / T 39600-2021 "Classification of formaldehyde emission of wood-based panels and their products", the water resistance and formaldehyde emission of the board are tested, and the results are shown in Table 6;

[0088] Table 6 Water resistance test results of seven-layer plywood

[0089]

[0090] Example 11: Preparation of adhesive using tris(2-aminoethyl)amine and glucose as raw materials

[0091] 1. Preparation of the adhesive of the present invention and preparation of plywood

[0092] (1) At room temperature, accurately weigh 18 g of glucose, mix and dissolve the glucose with deionized water to prepare a uniform aqueous solution with a mass concentration of 56.3%;

[0093] (2) adding 4.38 g of tris(2-aminoethyl)amine to the glucose solution in step (1), and placing the mixture in a 60° C. water bath for reaction for 10 min to obtain a reducing sugar-fatty amine adhesive;

[0094] (3) Use 2mm thick poplar veneer to press three-layer plywood (the glue amount is 320g / m 2 , hot pressing time is 6 minutes, hot pressing temperature is 120℃, hot pressing pressure is 1.0MPa), and the water resistance of the board is tested in accordance with the national standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels";

[0095] This example uses the method disclosed in the document "Novel hyperbranched resin for wood adhesive: Based on onair oxidation and crosslinking copolymerization strategy." Polymer Testing 126 (2023): 108154." as a control, and compares with the data disclosed in the document; the results are shown in Table 7;

[0096] Table 7 Water resistance test results of three-layer plywood

[0097]

[0098] From the results in Table 7, it can be seen that the water resistance of the plywood prepared by the adhesive prepared by the method of the present invention at a low hot pressing temperature (120°C) is comparable to the water resistance of the plywood prepared by the adhesive in the literature at a high hot pressing temperature (200°C). The reason is that the adhesive of the present invention does not rely on the oxidation of sugar at high temperature, while the method in the literature relies on the oxidation of sugar during the reaction (80°C, 2h) and high temperature hot pressing (200°C). The chemical basis of the adhesive prepared by the method of the present invention is completely different from that of the method in the literature. Comparative Example 1: Preparation of Adhesive Using Ethylenediamine and Glucose as Raw Materials

[0099] (1) At room temperature, accurately weigh 8 g of glucose, mix and dissolve the glucose with deionized water to prepare a uniform aqueous solution with a mass concentration of 50%;

[0100] (2) Add 4 g of ethylenediamine to the glucose solution in step (1), and place the mixture in a 60° C. water bath for reaction for 10 min to obtain a reducing sugar-fatty amine adhesive.

[0101] Comparative Example 2: Preparation of adhesive using triethylenetetramine and glucose as raw materials

[0102] (1) At room temperature, accurately weigh 8 g of glucose, mix and dissolve the glucose with deionized water to prepare a uniform aqueous solution with a mass concentration of 50%;

[0103] (2) Add 4 g of triethylenetetramine to the glucose solution in step (1), and place the mixture in a 60° C. water bath for reaction for 10 min to obtain a reducing sugar-fatty amine adhesive.

[0104] The adhesives prepared in Comparative Examples 1-2 were respectively used to press three-layer plywood (the amount of glue applied was 250g / m 2, hot pressing time is 6 minutes, hot pressing temperatures are 120°C and 140°C respectively, and hot pressing pressure is 1.0MPa), and the water resistance of the board is tested in accordance with the national standard GB / T 17657-2022 "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels", and the results are shown in Table 9;

[0105] Table 9 Water resistance test results of three-layer plywood

[0106]

[0107] The above results show that the properties of the reaction products of diamines or linear polyethylene polyamines containing adjacent amino groups and reducing sugars are different from those of the hexamethylenediamine-reducing sugar, melamine-hexamethylenediamine polymer-reducing sugar and other systems of the present invention, especially the ethylenediamine-glucose reaction product does not solidify even when kept at 120°C for 2 hours ( Fig.13 ); The above results show that the fatty amine structure has a significant effect on the formation and performance of the final adhesive.

Claims

1. A reducing sugar-fatty amine adhesive, characterized in that: The adhesive is prepared by adding fatty amine to a reducing sugar aqueous solution with a mass concentration of 20-60%, mixing well, reacting in a 40-60° C. water bath for 10-60 minutes or stirring at room temperature for 24-48 hours.

2. The reducing sugar-fatty amine adhesive according to claim 1, characterized in that: The mass ratio of fatty amine to reducing sugar is 1:0.5-5.

0.

3. The reducing sugar-fatty amine adhesive according to claim 1, characterized in that: The reducing sugar is one of glucose, maltose, galactose, fructose, mannose, hydrolyzed starch, hydrolyzed cellulose, hydrolyzed sucrose, hydrolyzed peach gum, and hydrolyzed cane molasses.

4. The reducing sugar-fatty amine adhesive according to claim 1, characterized in that: The fatty amine is a diamine having no adjacent amino groups in the carbon chain or a branched polyamine having no adjacent active hydrogen-containing amino groups in the carbon chain.

5. The reducing sugar-fatty amine adhesive according to claim 4, characterized in that: The fatty amine is 1,6-hexanediamine, tris(2-aminoethyl)amine or melamine-1,6-hexanediamine polymer.

6. The reducing sugar-fatty amine adhesive according to claim 5, characterized in that: The melamine-1,6-hexanediamine polymer is prepared by reacting melamine and 1,6-hexanediamine at 180-220° C. in the presence of an acidic catalyst, wherein the molar ratio of melamine to 1,6-hexanediamine is 1.0:2.0-4.

0.

7. The reducing sugar-fatty amine adhesive according to claim 1, characterized in that: The curing temperature is 100-140°C.

8. Use of the reducing sugar-fatty amine adhesive according to any one of claims 1 to 7 in bonding wood and bamboo materials.

Citation Information

Patent Citations

  • Maltose-based hyperbranched boiling-water-resistant adhesive and preparation method thereof

    CN115785899A

  • Lactosyl hyperbranched boiling-water-resistant adhesive and preparation method thereof

    CN117757417A